Stereotyper och rasbegreppet i finlandssvenska läroböcker: En textnära komparation av beskrivningar av samer under fyra decennier - Spjut, Lina (Umeå universitet, 2019)
Textbooks are in this article seen as reflections on values and ideas of its present. Often, it’s the majority’s culture and narrative that are told in a nation’s textbooks. What happens when one minority’s textbooks describe another minority? In Finland such a study is possible, since their Swedish-speaking minority, Finland-swedes, have their own tradition of textbook-production. This article analyses textbooks-quotes about Sami, a Finnish minority-group. The textbooks in question are written 1963, 1972, 1981 and 1997, for the Finnish minority-group, Finland-swedes. The aim of the article is to, by comparison, enlighten and analyse how and why one minority’s textbook describes another minority during four decades of status-change for minorities in Finland. Questions raised are i) How do textbooks for the Finland-swedes describe Sami-people, another marginalized minority during a period of 40 years? ii) Which identity-markers and concepts are in focus in textbook-descriptions? iii) What changes or stagnations are seen in textbooks and what factors could have made impact on the textbook-content over time?Results show that the first three books are reproduced intertextual but with an out-fading of stereotypical identity concepts which reflects a change from a biological definition of ethnicity to a more social definition. Although the concept ‘race’ appears in the textbooks from 1997, which can be caused by new race-debates, combined with change in the status of both Finland-swedes and Sami’s in Finland in the beginning of 1990s. The article argues that a marginalisation of Finland-swedes, as the same time as Sami’s got recognition as Finland’s indigenous people, made it important to connect Finns and Swedes as the common people – the common race – in order to get acknowledged as a natural part of Finlands population. In other words: When a majority culture defines and narrows down what is included in a national identity, it effects the minorities at several levels.